Electrical Properties of High-k Ta205 Gate Dielectrics on Strained Ge-rich Layers - PEROVA, TANIA; MOORE, ALAN (IEEE, 2004)
The electrical properties of ultrathin high-k Zr02 gate dielectric films dcposited on strained Gc-rich layers using microwave plasma enhanced chemical vapor deposition (PECVD) technique at a low temperature (150'C) have been studied. The strained Ge-rich heterolaycrs have been analyzed by transmission elcctron microscopy (TEM) and Raman spectra. X-ray photoclectron spectroscopy (XPS) has been used for analysis of chemical compositions of the deposited 2102 films. The fixed oxide charge density (Qdq) and interface state density (D;,) are found to be 4.8 x 10" cm~ 2an d 5 . 1 ~ 1 0 e' ~V -'mi2, respectively. The capacitance-voltage (C-V) characteristics and current-voltage (I-V) characteristics before and after constant current stressing exhibit good electrical properties and thus indicate the suitability of these films for future microelectronic applications.
PUBLISHED
Keywords: Mechanical and Manufacturing Engineering